The Effect Of Problem-Based Learning On Critical Thinking Skills On IPS Spelling - Desy Arista Mustikasari (Social Landscape Journal, 2022)
Social Sciences learning in junior high school has not been able to develop critical thinking skills, various problems in learning are considered as a boring subject so as less stimulate learners to think critically and less able to solve problems. This study aims to determine the effect of PBL on critical thinking skills in the field of social sciences study. The orientation of the problem to be raised relates to the material of the socio-cultural change. The research was conducted with a quasi-experimental design. Data analysis using t test. The subjects of the study were students of class IX IPS in MTs Nurush Sholihin - Magetan. The resulting significance value is 0.00. The results showed that PBL can make the learning of social sciences effective and efficient, so that the students' critical thinking skills increase.